1966
DOI: 10.1071/ar9660387
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the survival of the non-parasitic stages of the cattle tick Boophilus microplus in three climatically dissimilar districts of North Queensland

Abstract: Survival of the non-parasitic stages of the cattle tick, Boophilus microplus (Canestrini), has been investigated over a period of 5 years in 25, 40, and 80 in. rainfall districts of north Queensland. Engorged ticks were exposed regularly in field plots and in Stevenson screens, and the times of egg hatchmg (prehatch period) and periods of survival of the larvae were observed. The prehatch period in the three districts followed the same pattern and was related to seasonal temperature changes, varying from less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1971
1971
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…The incidence of acaricide resistance is higher in one host ticks because a much larger fraction of the total population of such species remains under chemical challenge at any one time than multi host ticks. In addition to it, a single generation of multi-host tick may extend over up to 3 years compared to 2-3 months in one host tick (Harley 1966).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of acaricide resistance is higher in one host ticks because a much larger fraction of the total population of such species remains under chemical challenge at any one time than multi host ticks. In addition to it, a single generation of multi-host tick may extend over up to 3 years compared to 2-3 months in one host tick (Harley 1966).…”
Section: Resultsmentioning
confidence: 99%
“…microplus in areas outside the U.S. (Snowball, 1957;Wilkinson and Wilson, 1959;Hall and Wilkinson, 1960;Harley, 1966;McCulloch and Lewis, 1968;Cerny and de la Cruz, 1971;Owen, 1975;Sutherst, 1983, Sutherst et al, 1988Short et al, 1989;Garris et al, 1990). Most recent studies of the effects of temperature and humidity on oviposition and longevity in B. microplus ticks in the US have been conducted in the laboratory (Davey et al, 1980;Davcy and Cooksey, 1989;.…”
Section: Introductionmentioning
confidence: 99%
“…microplus reported by Hitchcock (1955); Snowball (1957); Wilkinson and Wilson ( 1959) ;Harley ( 1966) ; McCulloch and Lewis (1968) indicated that placing cattle in small, initially tick-free "disinfestation" paddocks (DP) for appropriate periods of time might free them of ticks. This method should be effective if cattle grazed a DP for a period of sufficient duration to allow all ticks on the animals to mature and fall, but too short to allow progeny of these ticks to hatch and reinfest the cattle, Ideally then, cattle would drop their tick burden in a DP, graze a major grazing paddock (MGP) until tick infestation approached an unacceptable level, drop these ticks in a DP and repeat this rotation indefinitely.…”
Section: Theorymentioning
confidence: 93%